Measurement of gamma-ray production cross sections for nuclear reaction 31P(p,pγ1-0)31P - Silva, Hugo (2020)
In order to implement a standard free PIGE analysis of phosphorus, the cross section of the reaction 31P(p,pγ1-0)31P, γ1-0=1266.1keV was measured for the proton energy range 2.6–4 MeV, with energy steps ranging from 1 keV on resonances to 10 keV off resonance. This data provides additional information in relation to previous works on this reaction, as a more detailed and extended (in energy) measurement was made. The results obtained in this work were compared within the common energy range with previous measurements. There is a fair agreement within the quoted uncertainties although a larger energy step was used by the other authors and some resonances were missed. Also, a validation was accomplished by introducing the measured excitation function in the ERYA code to calculate thick target phosphorus yields of Ca3(PO4)2 and comparing the calculated values with the corresponding measured yields and also with other thick target yields found in the literature. A good agreement was found.